Comparison of Early and Late Fetal Extraction on Maternal Outcome in Placenta Accreta Spectrum - Taymour, Mohammad A.; Alasmer, Amira; Mahmoud, Ahmed; Ibrahim Fawzy, Ibrahim Fawzy; Mansi, Yasmeen; El-Kateb, Abdalla Y. (Journal of Neonatal Surgery, 2025)
Background: Placenta accreta spectrum (PAS) is one of the devastating obstetric complications owing to massive bleeding that may lead to peripartum hysterectomy, need for massive blood transfusion, maternal intensive care admission and maternal mortality. The aim of this work was to investigate the effect of late fetal extraction on the maternal and neonatal outcomes in patients diagnosed with PAS. Methods: This prospective cohort study was carried out on 60 pregnant women with age from 18 to 40 years old with PAS diagnosed by ultrasound, operative findings and histopathological examination. Patients were divided into two equal groups: Group (A): Late fetal extraction and Group (B): Early fetal extraction. Results: Time from induction of anesthesia to peritoneal entry and from peritoneal entry till cord clamping were significantly higher in group (A) than group (B) (P <0.001). Blood loss, blood transfusion and bladder injuries were significantly lower in group (A) compared to group (B) (P<0.05). Hospital stay and intensive care unit admission were insignificantly different between both groups. In both groups no cases of maternal mortalities, the estimated fetal weight, APGAR score at 1 min and 5 min, neonatal intensive care unit and neonatal respiratory support were insignificantly different between both groups. Conclusions: The late fetal extraction technique was superior to early fetal extraction as it showed lower blood loss, blood transfusion and lower bladder injury for cases with PAS without affecting neonatal outcome.